2010
DOI: 10.1088/0022-3727/43/18/185101
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Mg-doped and In–Mg co-doped p-type GaN epitaxial layers grown by metal organic chemical vapour deposition

Abstract: Mg-doped and In-Mg co-doped p-type GaN epilayers were grown using the metal organic chemical vapour deposition technique. The effect of In co-doping on the physical properties of p-GaN layer was examined by high resolution x-ray diffraction (HRXRD), transmission electron microscopy (TEM), Hall effect, photoluminescence (PL) and persistent photoconductivity (PPC) at room temperature. An improved crystalline quality and a reduction in threading dislocation density are evidenced upon In doping in p-GaN from HRXRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…The enhanced dopant solubility by using In surfactant was also confirmed by the other research groups. 9,10) It has been found that when In is fed into the reactor, the incorporation efficiency of Ga atoms is decreased sharply, bringing a higher effective V/III ratio at the growing surface and therefore a decrease of nitrogen vacancy (V N ) in the epilayer. 10) Moreover, the decreased Ga incorporation can provide III-group vacancies to be occupied by Mg atoms, improving the incorporation efficiency of Mg atoms.…”
mentioning
confidence: 99%
“…The enhanced dopant solubility by using In surfactant was also confirmed by the other research groups. 9,10) It has been found that when In is fed into the reactor, the incorporation efficiency of Ga atoms is decreased sharply, bringing a higher effective V/III ratio at the growing surface and therefore a decrease of nitrogen vacancy (V N ) in the epilayer. 10) Moreover, the decreased Ga incorporation can provide III-group vacancies to be occupied by Mg atoms, improving the incorporation efficiency of Mg atoms.…”
mentioning
confidence: 99%
“…In this work, extremely high V/III ratios (10000:1) and high growth temperatures (1050 °C) are used to yield sufficient amounts of active nitrogen species for gallium nitride growth, which is helpful for ammonias cracking and transport of atomic N to proper lattice sites. The strain analyses by XRD published by our group previously have confirmed the elimination of nitrogen vacancies in Indium doped nitrides by using non-equilibrium growth techniques24, which is consist with the results of Chung25. To get more effective p doping for nitrides, better approaches to suppress N vacancy are still highly desired.…”
Section: Discussionmentioning
confidence: 56%
“…The Mg concentration increased from 8.8 × 10 18 cm −3 to 1.2 × 10 19 cm −3 when using indium‐surfactant‐assisted δ‐doping, which plays a key role in the enhancement of hole concentration. It has been proposed that when In is fed into the reactor, the incorporation efficiency of Ga atoms may be decreased sharply, resulting in the higher effective V/III ratio in the growth interface and the subsequent suppression of V N . In addition, since the binding energy of the InN bond (1.98 eV) is lower than that of the GaN bond (2.20 eV) , In atoms are preferentially desorbed from the surface during the purge step of δ‐doping as compared with the Ga atoms .…”
Section: Resultsmentioning
confidence: 99%